Structural control of wind turbines with soil structure interaction included. (15th March 2016) - Fitzgerald, Breiffni; Basu, Biswajit
Highlights: Soil–structure interaction (SSI) is considered in a structural control scheme for wind turbines. SSI has a negligible effect on blade vibrations. Active tuned mass dampers (ATMDs) are shown to respond well to changes in system frequencies due to presence of SSI. Passive structural control techniques can be rendered ineffective when SSI is considered. Abstract: The importance of considering soil structure interaction in structural control of wind turbines is investigated in this paper. An Euler–Lagrangian wind turbine mathematical model based on an energy formulation was developed for this purpose which considers the structural dynamics of the system and the interaction between in-plane and out-of-plane blade vibrations. Also, the interaction between the blades and the tower including a tuned mass damper (TMD) is considered. The turbine is subject to turbulent aerodynamic loading simulated using a modification to the classic Blade Element Momentum (BEM) theory with turbulence generated from rotationally sampled spectra. The turbine is also subject to gravity loading. The effect of centrifugal stiffening of the rotating blades has also been considered. The developed wind turbine model has been benchmarked against the NREL's aeroelastic model FAST. Three-dimensional models of the wind turbine foundation are designed and analysed in the finite element geotechnical code Plaxis. Bi-axial rotations of the foundation obtained from dynamic finite element analyses are used to calculate rotational spring constants. These spring constants are used in the wind turbine model to describe the soil–structure interaction (SSI) between the wind turbine foundation and the underlying soil medium. This paper shows that where there are uncertainties regarding the stiffness of the soil, passive vibration control schemes may be rendered ineffective. Furthermore, it is demonstrated that vibration control of wind turbines using the proposed active control scheme has a promising prospect in situations where soil parameter values are uncertain.